Lipoprotein(a) plasma levels, bone mineral density and risk of hip fracture: a post hoc analysis of the Women’s Health Initiative, USA - Haring, Bernhard (BMJ Open, 2019)
OBJECTIVES: Elevated Lipoprotein(a) (Lp[a]) is a well-known risk factor for cardiovascular disease. However, its roles in bone metabolism and fracture risk are unclear. We therefore investigated whether plasma Lp(a) levels were associated with bone mineral density (BMD) and incident hip fractures in a large cohort of postmenopausal women. DESIGN: Post hoc analysis of data from the Women’s Health Initiative (WHI), USA. SETTING: 40 clinical centres in the USA. PARTICIPANTS: The current analytical cohort consisted of 9698 white, postmenopausal women enrolled in the WHI, a national prospective study investigating determinants of chronic diseases including heart disease, breast and colorectal cancers and osteoporotic fractures among postmenopausal women. Recruitment for WHI took place from 1 October 1993 to 31 December 1998. EXPOSURES: Plasma Lp(a) levels were measured at baseline. OUTCOME MEASURES: Incident hip fractures were ascertained annually and confirmed by medical records with follow-up through 29 August 2014. BMD at the femoral neck was measured by dual X-ray absorptiometry in a subset of participants at baseline. STATISTICAL ANALYSES: Cox proportional hazards and logistic regression models were used to evaluate associations of quartiles of plasma Lp(a) levels with hip fracture events and hip BMD T-score, respectively. RESULTS: During a mean follow-up of 13.8 years, 454 incident cases of hip fracture were observed. In analyses adjusting for confounding variables including age, body mass index, history of hysterectomy, smoking, physical activity, diabetes mellitus, general health status, cardiovascular disease, use of menopausal hormone therapy, use of bisphosphonates, calcitonin or selective-oestrogen receptor modulators, baseline dietary and supplemental calcium and vitamin D intake and history of fracture, no significant association of plasma Lp(a) levels with low hip BMD T-score or hip fracture risk was detected. CONCLUSIONS: These findings suggest that plasma Lp(a) levels are not related to hip BMD T-score or hip fracture events in postmenopausal women. TRIAL REGISTRATION NUMBER: NCT00000611; Post-results.